A Philosophical Theory of the Politics of Space: Totalitarian Space and the Destruction of Spatial Aura - Ahmed, Saladdin (Université d'Ottawa / University of Ottawa, 2013)
The central argument advanced in this dissertation is that the production of totalitarian space relies on the systematic destruction of spatial aura. I begin by critically studying the term “totalitarian” with references to Hannah Arendt and Robert Conquest, and re-appropriating it based on relevant insights from Herbert Marcuse, Theodor Adorno and Max Horkheimer, Georg Lukács, and Slavoj Žižek. In the meantime, I introduce the Baath state in Syria and Iraq as an example of totalitarianism, and present a concise account of its ideological history. Here I also shed light on important aspects of Critical Theory, which will have a recurring role throughout the project. I then discuss spatial production by critically explicating Henri Lefebvre’s dialectical theory of the production of space, which claims that space is produced according to the dominant modes of production. However, despite its critical significance to my project, Lefebvre’s theory alone cannot account for totalitarian space. Therefore, after pausing on Lefebvre’s concepts of appropriated versus dominated spaces, I move to Michel Foucault’s work on the Panopticon as a major spatial technology of power and a generalizable formula in societies of control and discipline. I also introduce Foucault’s heterotopia and Gaston Bachelard’s poetic space as counter examples to totalitarian space. Indeed, I argue that Lefebvre’s appropriated space, Foucault’s heterotopia, and Bachelard’s poetic space all have something in common. Aura, with its inherent negativity, is precisely the concept to indicate such spatial uniqueness, the systematic elimination of which is definitive of totalitarian space. In addition to critically exploring Walter Benjamin’s definitions of aura and developing his secularized notion of it, I also focus on his claim that mechanically reproduced works of art lack aura. This then brings me to the last stage of my project where I argue that mechanically reproduced images are not just auraless; they also destroy the aura of space. Finally, by way of illustration, I turn back to the example of the Baath state and analyze the use of mechanically reproduced images of the leader as destroyers of spatial aura and thus crucial components of the production of totalitarian space.
Keywords: aura; space; totalitarianism; spatial aura; production of space; philosophy; Critical Theory